The Effectiveness of Using Short Movies to Improve Vocabulary Mastery: A Pre-Experimental Research at Class VII-H of SMP A. Wahid Hasyim Tebuireng Jombang in the Academic Year of 2023-2024 - Ail, Lailatussholichah; Ria Kamilah Agustina (Bilingua, 2023)
The objective of this research is to find out whether or not the implementation of short movies media effective to improve the students’ vocabulary mastery. The researcher conducted a pre-experimental group design. The population of this research is the seveth-grade students of SMP A. Wahid Hasyim Tebuireng Jombang in the academic year 2023/2024. Total of the population was 9 classes. The sample in this study was class VII H SMP A. Wahid Hasyim Tebuireng Jombang, totaling 32 students. Based on the data normality test that has been carried out by the researcher, it shows that sig. 2-tailed is 0.200 meaning that the data is normally distributed, then it will be continued with a simple paired t-test. based on the Testing of Hypothesis Terms, If the score of t is sig. <0.05, Ha is accepted and H0 is rejected. on the simple paired t-test calculation, the data shows sig. (2-tail) 0.000. The data is smaller than 0.05, meaning that H0 is rejected and Ha is accepted. the students' scores of pre-test was in medium level, while in post-test, the students' score was high. it could be concluded that the short movies was effective to improve students' vocabulary mastery in SMP A. Wahid Hasyim Tebuireng Jombang.